Jubilate: a conversation about Prayer Book revision and the language of our prayer - Meyers, Ruth A. (Anglican theological review, 2021)
These essays were presented at the Jubilate conference at Christ Church Cathedral in the Diocese of Southern Ohio on 2 November 2019. Meyers urges the expansion of images and metaphors used to speak of the mystery of God in liturgy while not abandoning classical masculine language for God. Expanding our language is essential, she argues, both to speak the truth about God and to uphold the dignity of every human being. Sonderegger contends that masculine language for God is a settled matter in the church and in liturgy, and that this is compatible with a particular vision of Christian feminism, one centered on the material conditions of living women.